The effect of implicit and explicit practice in the development of decision making in volleyball serving - Lola, A. C.; Tzetzis, G. C.; Zetou, H. (Perceptual and Motor Skills, 2012)
This experiment investigated the effect of explicit, implicit, and sequential learning (implicit-explicit) on the acquisition and retention of decision-making skill in volleyball. The participants were 60 female novices, ages 10 to 12 years. The experimental groups followed three different methods of training: (a) explicit practice for the development of declarative knowledge, (b) implicit practice for the development of the procedural knowledge, (c) sequential practice (implicit first and then explicit), and (d) control group that participated only in the measurements. A pre-test, a post-test, and a retention test measured the response time and accuracy of the decision-making skill. Analysis indicated that all experimental groups improved over time while the control group did not. The sequential group was faster and more accurate than the implicit group, and the latter was faster and more accurate than the explicit one. The sequential group outperformed implicit and explicit groups on both speed and accuracy of decision. It seems that both explicit and implicit processes, when they take place in sequence, interact positively, and this method improves speed and accuracy of decision making rather than when each mode of learning (implicit or explicit) occurs separately. If the role of working memory is reduced at the early stages of learning, the accumulation of declarative knowledge (explicit learning) may benefit from accumulation of procedural knowledge and enhance decision-making skill.